2007
DOI: 10.1109/tnsre.2007.903917
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of a Rehabilitation Robotic Exoskeleton for Tremor Assessment and Suppression

Abstract: Exoskeletons are mechatronic systems worn by a person in such a way that the physical interface permits a direct transfer of mechanical power and exchange of information. Upper limb robotic exoskeletons may be helpful for people with disabilities and/or limb weakness or injury. Tremor is the most common movement disorder in neurological practice. In addition to medication, rehabilitation programs, and deep brain stimulation, biomechanical loading has appeared as a potential tremor suppression alternative. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
232
2
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 301 publications
(239 citation statements)
references
References 16 publications
0
232
2
5
Order By: Relevance
“…First, mechanical systems were tested on body limbs to add mechanical resistance, such as inertial load [7][8], viscous load [9], and both inertial and viscous load [10], which reduced tremor by 40-80% [7][8][9][10]. However, mechanical systems are not entirely prepared to be used in daily life, because they are bulky, with burdensome weight, and not aesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…First, mechanical systems were tested on body limbs to add mechanical resistance, such as inertial load [7][8], viscous load [9], and both inertial and viscous load [10], which reduced tremor by 40-80% [7][8][9][10]. However, mechanical systems are not entirely prepared to be used in daily life, because they are bulky, with burdensome weight, and not aesthetic.…”
Section: Introductionmentioning
confidence: 99%
“…The term "exoskeleton" refers to any electromechanical system that can be worn by a person to replicate the anatomical configuration of the corresponding parts of the body, in order to enhance the power of muscles by a direct transfer of mechanical energy from the device to the human [1][2][3]. The history of creation of external auxiliary equipment dates back to the 19 th century, when a Russian inventor Yagn developed the "elastiped" -a device for making walking, running and jumping easier [4].…”
Section: Historical Backgroundmentioning
confidence: 99%
“…The EMD was set to 20 ms (according to the results presented below); the antagonist pair was co-contracted for a time period equivalent to 30 • . Tremor attenuation was computed as the ratio of the integral of the power spectral density (PSD) of the tremor in the second sub-period of the trial to the same variable calculated in the first sub-period (R att ) [13,9], and reported as percentage. The pooled values of R att for the ST and NO trials were compared using a Mann-Whitney test, to assess whether the control strategy attained a significant tremor attenuation.…”
Section: B Pilot Testing Of the Tremor Suppression Strategymentioning
confidence: 99%